The Politics of Women's Health Care in the United States - Palley, Marian Lief.; Palley, Howard A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2014)
A look at how the women's health agenda has been reframed in the past several decades.
Keywords: Social sciences; Political science; Social policy; Sociology; Political sociology; Sex (Psychology).; Gender expression; Gender identity; Social Sciences; Social Policy; Political Sociology; Political Science; Gender Studies; Social Policy; Sociology, general